Penerapan Whole Of Government Dalam Layanan Terpadu Satu Atap (LTSA-PMI) Di Kota Samarinda - Yehezkiel Yehezkiel; Muhammad Hairul Saleh; Jauchar Barlian (Journal of Innovation Research and Knowledge, 2026)
Protection of Indonesian Migrant Workers (PMI) is a cross-sectoral governance issue because the placement and protection process involves aspects of employment, population administration, health, immigration, security, social security, and administrative services. This complexity requires the government to develop service delivery mechanisms that are not fragmented across institutions. One of the instruments developed for this purpose is the One-Stop Integrated Service for Indonesian Migrant Workers (LTSA-PMI), which conceptually reflects a whole-of-government approach by integrating various government institutions within a single service mechanism. This study aims to analyze the implementation of the whole-of-government approach in the delivery of LTSA-PMI services in Samarinda City and to identify factors that support and hinder service integration. The study employs a qualitative approach with a case study design. Data were obtained through analysis of policy documents, regulations, local government documents, and relevant scientific literature, and may be strengthened through interviews with LTSA-PMI service providers. The analysis focuses on the dimensions of institutional integration, coordination, distribution of authority, information exchange, resources, and user-oriented service delivery. The analysis shows that, institutionally, LTSA-PMI has considerable potential as an instrument for implementing whole-of-government principles because it brings together various government organizations within an integrated service process for the placement and protection of Indonesian migrant workers. However, institutional integration does not automatically result in substantive integration. Challenges such as sectoral ego, differences in authority, resource capacity, information interoperability, and dependence on inter-agency coordination can affect the quality of implementation. Therefore, the implementation of whole-of-government in LTSA-PMI needs to move beyond merely consolidating service counters toward the integration of processes, data, authority, and inter-agency accountability. This study emphasizes that the success of LTSA-PMI as a whole-of-government model is largely determined by the government's ability to establish sustainable coordination that is responsive to the needs of Indonesian migrant workers.